Update on metal-induced occupational lung disease. Issue 2 (April 2018) - Wyman, Anne E.; Hines, Stella E.
Abstract : Purpose of review: Occupational and environmental exposures to metals can result in multiple pulmonary conditions. This article will review recent epidemiologic and mechanistic studies that have enhanced our understanding of the association between particular lung diseases and exposure to specific metals. Recent findings: Recent studies have broadened our understanding of the mechanisms of lung diseases such as CBD in established industries and drawn attention to conditions that may arise from exposure to metals such as indium in developing technologies. New diagnostic techniques such as elemental tissue analysis may help establish a diagnosis of metal-induced occupational lung disease. Electronic cigarette devices, environmental pollutants, and the growing use of nanoparticle-sized metals pose additional risks to workers and consumers. Summary: Recognizing the risks of pulmonary disease in workers exposed to metals and performing a thorough occupational history and diagnostic work-up in patients with unexplained respiratory findings is necessary to promote understanding and prevention of metal-induced lung disease.